Designing Evidence-Based Family Planning Programs for the Marginalized Community: An Example of Muslim Community in Nepal - Sapkota, Diksha; Adhikari, Shiva Raj; Bajracharya, Tara; Sapkota, Vishnu Prasad (Frontiers in Public Health, 2016)
Context: Family planning, considered as an encouraging trend for development, is thought to be positively correlated with family health and well-being and negatively correlated with poverty levels. Despite being a priority goal of government and development agencies, in a heterogeneous society like Nepal, family planning can be an issue needs to be dealt with consideration for religious and cultural beliefs of different sections of society. Despite steady progress in achieving family planning goals, minority populations have lagged behind the rest of the country in achieving improved family health outcomes; Muslim community being one such example. Objectives: This study aimed to explore the existing situation of family planning use in Muslim communities and to identify key policy related issues affecting the access to and utilization of family planning services. Settings and Design: Mixed approach was used in Kapilbastu district which accommodated the larger proportion of Muslims in Nepal. Methods and Material: Interview was conducted among 160 married women using semi-structured questionnaire. Focus group discussion, key informant interviews and consultative meeting were the qualitative techniques employed in this study. Quantitative data were analysed using descriptive and inferential statistics (Chi square test) while qualitative data by thematic approach. Results: More than half of women (56.0%) expressed their interest in family planning use while reported users were just below the quarter (24.0%). Husband approval and secrecy of their personal identity affect use of any method of contraception. Future plan for children and prior information regarding family planning found to affect current use of family planning significantly. Family planning word itself was found to be stigmatising so women prefer replacing the word family planning with culturally appropriate one. Furthermore, incorporating it into comprehensive package for improving women’s health will definitely contribute to improve access and uptake of services. Conclusions: Discrepancy exists between current use and desire for use of family planning among Muslim women in future. This highlights the inadequacy of implementing the current blanket policy and programs related to family planning and offer ways to move forward with the national family planning agenda ensuring the cultural rights and non-discrimination of women.